Microcannula Utilization for Injectable Facial Fillers: Standard of Care?. Issue 4 (December 2018) - Karimi, Kian; Griffiths, Chester F.; Reivitis, Alex; Davis-Hunter, Austin; Zhang, Elizabeth; Pourang, Dorna
The microcannula technique has become an increasingly popular method for injecting cosmetic fillers. Previous studies have illustrated that the microcannula technique allows filler to be injected with less pain, swelling, and essentially no bruising. This study is a retrospective clinical series examining 247 patients who have undergone dermal filler injections using the microcannula technique from 2011 to 2016 with a single injector, Kian Karimi. The purpose of this study is to assess the frequency of adverse events associated with injections such as bruising and swelling. All 666 recorded patient visits from 2011 to 2016 were analyzed using electronic medical records based on the criteria that the patients had cosmetic filler using the microcannula technique by the surgeon investigator. Of the 666 filler treatments using the microcannula technique, 3 treatments (0.5%) produced adverse events on the day of service, and 32 treatments (4.8%) produced adverse events at 2-week follow-up. In total, 5.4% of treatments produced adverse events. At the 2-week follow-up, 5.7% of treatments using the 25-gauge microcannula produced adverse events ( P = .830); 3.9% of treatments using the 27-gauge microcannula produced adverse events ( P = .612]). Only 3 patients were treated with the 30-gauge microcannula, and 1 patient reported adverse events on the day of service. None of the treatments using the 30-gauge microcannula produced adverse events at the 2-week follow-up ( P = .160). The data support that the microcannula technique is a safe and effective alternative to hypodermic needles for the injection of dermal filler to minimize common adverse events.